Changes in the gut bacteriome upon gluten-free diet intervention do not mediate beta cell preservation - Neuman, Vit; Pruhova, Stepanka; Kulich, Michal; Kolouskova, Stanislava; Vosahlo, Jan; Romanova, Martina; Petruzelkova, Lenka; Havlik, Jaroslav; Mascellani, Anna; Henke, Svatopluk; Sumnik, Zdenek; Cinek, Ondrej (Diabetologia, 2023)
AIMS/HYPOTHESIS: We previously detected indications that beta cell function is protected by gluten-free diet (GFD) introduced shortly after the onset of childhood type 1 diabetes. The present aim was to assess whether GFD was associated with changes in the gut bacteriome composition and in its functional capacity, and whether such changes mediated the observed effects of GFD on beta cell function. METHODS: Forty-five children (aged 10.2 ± 3.3 years) were recruited into a self-selected intervention trial primarily focused on determining the role of GFD on beta cell preservation ( ClinicalTrials.gov NCT02867436). Stool samples were collected prior to the dietary intervention and then at 3-month intervals. A total of 128 samples from the GFD group and 112 from the control group were analysed for bacteriome 16S rDNA community profiles, the bacteriome functional capacity was predicted using PICRUSt2 and actual gut metabolome profiles measured using NMR. Intestinal permeability was assessed using serum zonulin concentrations at 1, 6 and 12 months and lactulose/mannitol tests at the end of intervention. Dietary questionnaires were used to ensure that the dietary intervention did not result in differences in energy or nutrient intake. RESULTS: The bacteriome community composition changed during the intervention with GFD: of abundant genera, a 3.3-fold decrease was noted for Bifidobacterium genus (adjusted p=1.4 × 10-4 in a DESeq2 model, p=0.026 in generalised estimating equations model), whereas a 2.4-fold increase was observed in Roseburia (adjusted p=0.02 in DESeq2 model, p=0.002 in generalised estimating equations model). The within-sample (alpha) diversity did not change, and there was no statistically significant clustering of GFD samples in the ordination graphs of beta diversity. Neither of the genera changes upon GFD intervention showed any association with the pace of beta cell loss (p>0.50), but of the remaining taxa, several genera of Bacteroidaceae family yielded suggestive signals. The faecal metabolome profile ordination correlated with that of bacteriomes but did not associate with GFD or categories of beta cell preservation. There was no indication of changes in gut permeability. CONCLUSIONS/INTERPRETATION: The bacteriome reacted to GFD, but the changes were unrelated to the pace of beta cell capacity loss. The previously observed moderately protective effect of GFD is therefore mediated through other pathways.
Keywords: Gluten-free diet; Gut metabolome; Intestinal permeability; Paediatric type 1 diabetes; Humans; Gut bacteriome composition; bezlepková dieta; Diet, Gluten-Free; dítě; lidé; Child